The Importance of Resistance Training in Addressing Insulin Resistance and Type 2 Diabetes: A Narrative Review - Siwicka, Katarzyna; Szewczyk, Konrad; Janasik, Laura; Kociucka, Patrycja; Sadowski, Krzysztof; Modelska, Julia; Jeleń, Anita; Podolska, Anna; Paluchowicz, Karolina (Quality in Sport, 2026)
Introduction: Insulin resistance and type 2 diabetes mellitus are serious global health challenges, which are caused by aging population, increasing levels of obesity and insufficient amount of physical activity. Although pharmacological treatment is still a central part of managing diabetes, a substantial number of patients are not able to achieve optimal glycemic control, showing the need for effective lifestyle interventions. Resistance training has become a promising strategy which targets main pathophysiological mechanisms underlying insulin resistance. Purpose: This narrative review aims to summarize and critically evaluate current evidence on the effects of resistance training on insulin sensitivity, metabolism of glucose and cardiometabolic health across diverse populations, including patients with type 2 diabetes, insulin resistance, obesity, metabolic syndrome, and older adults. Material and Method: A comprehensive literature search was conducted using the PubMed/MEDLINE database and included studies published up to 2025. Only peer-reviewed articles written in English were included in the review. Particular emphasis was placed on randomized controlled trials, systematic reviews, and meta-analyses. Results: Evidence from randomized controlled trials and meta-analyses demonstrates that resistance training improves glycemic control, reduces insulin resistance as well as enhances body composition and functionality. Comparative analyses indicate that resistance training provides benefits that are complementary to aerobic exercise, dietary interventions, and pharmacotherapy, particularly when weight loss strategies are added. Conclusions: The findings support resistance training as a safe and effective component of comprehensive management strategies for insulin resistance and type 2 diabetes.